2022
DOI: 10.3390/biology11030442
|View full text |Cite
|
Sign up to set email alerts
|

ATP Purinergic Receptor P2X1-Dependent Suicidal NETosis Induced by Cryptosporidium parvum under Physioxia Conditions

Abstract: Cryptosporidiosis is a zoonotic intestinal disease that affects humans, wildlife, and neonatal cattle, caused by Cryptosporidium parvum. Neutrophil extracellular traps (NETs), also known as suicidal NETosis, are a powerful and ancient innate effector mechanism by which polymorphonuclear neutrophils (PMN) battle parasitic organisms like protozoa and helminths. Here, C. parvum oocysts and live sporozoites were utilized to examine suicidal NETosis in exposed bovine PMN beneath both 5% O2 (physiological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 89 publications
(198 reference statements)
0
15
0
Order By: Relevance
“…Moreover, the gut is a distinct niche from other organs with its own physioxia, also described as normoxia, and with it being the largest human organ surface with numerous commensals, micro-and macroorganisms [79][80][81]. Physioxia has been shown to have implications not only in the production of C. parvum-triggered NETs [82] but also in the metabolism of bovine small intestinal explants (BSI) and primary bovine intestinal epithelial cells (BSIECs) infected with C. parvum [52,53]. Knowing this fact, the metabolic profile of suicidal METosis induced by C. parvum was investigated under two different oxygen conditions, namely physioxia (5% O 2 ) and hyperoxia (21% O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the gut is a distinct niche from other organs with its own physioxia, also described as normoxia, and with it being the largest human organ surface with numerous commensals, micro-and macroorganisms [79][80][81]. Physioxia has been shown to have implications not only in the production of C. parvum-triggered NETs [82] but also in the metabolism of bovine small intestinal explants (BSI) and primary bovine intestinal epithelial cells (BSIECs) infected with C. parvum [52,53]. Knowing this fact, the metabolic profile of suicidal METosis induced by C. parvum was investigated under two different oxygen conditions, namely physioxia (5% O 2 ) and hyperoxia (21% O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, polymorphonuclear leukocyte cells (PMN)s isolated from C. parvum -infected mice were shown to play a role in converting resident macrophages to M1 macrophages. Another possible mechanism is through NETosis, an effector mechanism by which extracellular fibers (primarily DNA) from neutrophils bind pathogens ( Hasheminasab et al, 2022 ). In one study, neutrophil extracellular traps (NETs) were found to form when bovine neutrophils were incubated with either sporozoites or oocysts.…”
Section: Neutrophilsmentioning
confidence: 99%
“…1, Ref. [24][25][26][27][28][29][30][31][32]). Microbial barrier, mucus barrier [33], epithelial barrier [33], vascular barrier [34], and immune barrier [33] in the intestinal tract can resist the invasion of harmful substances from the external intestinal environment.…”
Section: Intestinal Flora and Its Metabolites Can Modulate Risk Of Tu...mentioning
confidence: 99%
“…Intestinal flora disorder is common in patients with CRC. Short-chain fatty acids can regulate intestinal flora [32]. Recent studies have found that SCFAs, such as butyric acid can also inhibit the proliferation of cancer cells or participate in immune regulation, hence achieve anti-tumor effects [44].…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
See 1 more Smart Citation